Primary Immunodeficiencies in Russia: Data From the National Registry - Mukhina, Anna A.; Kuzmenko, Natalya B.; Rodina, Yulia A.; Kondratenko, Irina V.; Bologov, Andrei A.; Latysheva, Tatiana V.; Prodeus, Andrei P.; Pampura, Alexander N.; Balashov, Dmitrii N.; Ilyina, Natalya I.; Latysheva, Elena A.; Deordieva, Ekaterina A.; et al. (Frontiers in Immunology, 2020)
Primary immunodeficiencies (PID) are a group of rare genetic disorders with a multitude of clinical symptoms. Characterization of epidemiological and clinical data via national registries has proven to be a valuable tool of studying these diseases. Materials and Methods. The Russian PID registry was set up in 2017, by the National Association of Experts in PID (NAEPID). It is a secure, internet-based database that includes detailed clinical, laboratory and therapeutic data on PID patients of all ages. Results. The registry contained information on 2728 patients (60% males, 40% females), from all Federal Districts of the Russian Federation. 1851/2728 (68%) were alive, 1426/1851 (77%) were children and 425/1851 (23%) were adults. PID was diagnosed before the age of 18 in 2192 patients (88%). Antibody defects (699; 26%) and syndromic PID (591; 22%) were the most common groups of PID. The minimum overall PID prevalence in the Russian population was 1.3:100,000 people; the estimated PID birth rate is 5.7 per 100,000 live births. The number of newly diagnosed patients per year increased dramatically, reaching the maximum of 331 patients in 2018. The overall mortality rate was 9.8%. Genetic testing has been performed in 1740 patients and genetic defects were identified in 1344 of them (77.2%). The median diagnostic delay was 2 years; this varied from 4 months to 11 years, depending the on the PID category. The shortest time to diagnosis was noted in the combined PIDs—in WAS, DGS and CGD. The longest delay was observed in AT, NBS and in the most prevalent adult PID: HAE and CVID. Of the patients, 1622 had symptomatic treatment information: 843 (52%) received IG treatment, mainly IVIG (96%), and 414 (25%) patients were treated with biological drugs. HSCT has been performed in 342/2728 (16%) patients, of whom 67% are currently alive, 17% deceased and 16% lost to follow-up. Three patients underwent gene therapy for WAS; all are currently alive. Conclusions. Here we describe our first analysis of the epidemiological features of PID in Russia, allowing us to highlight the main challenges around PID diagnosis and treatment.